PENGARUH AFFILIATE MARKETING, INFLUENCER, DAN LIVE STREAMING TERHADAP KEPUTUSAN PEMBELIAN PRODUK FASHION ONLINE DI TIKTOK SHOP (STUDI PADA MAHASISWA DI UNIBA SURAKARTA) - Arba Ati Aktafia Sari (JURNAL ILMIAH EDUNOMIKA, 2026)
This study was conducted to examine and analyze the impact of Affiliate Marketing, Influencers, and Live Streaming on online fashion product purchasing decisions on TikTok Shop, with students from Universitas Islam Batik (UNIBA) Surakarta as the study subjects. The approach used in this research is quantitative with a causal-associative design. The population object includes UNIBA Surakarta students who have recorded having purchased fashion products online through TikTok Shop within the last six months; a total of 100 respondents were involved as a sample calculated using the Lemeshow formula and selected through a purposive sampling technique. Primary data collection was carried out using a 5-point Likert scale questionnaire instrument that had previously been tested for validity and reliability, then analyzed using the classical assumption test and multiple linear regression assisted by SPSS software. The study findings show that the variables Affiliate Marketing, Influencers, and Live Streaming have a positive and significant partial influence on purchasing decisions. Simultaneous testing also proved that the three independent variables had a significant influence on purchasing decisions (F count = 103.687; Sig. = 0.000), with the ability to explain variations in purchasing decisions by 75.7 percent (Adjusted R Square = 0.757). This finding confirms that influencer credibility, live streaming interactivity, and trust in the affiliate system together are the main determinants of fashion product purchasing decisions among students in the era of social media-based digital marketing. Keywords: Affiliate Marketing; Influencer; Live streaming; Purchase Decision; TikTok Shop